Healthy and Unhealthy Food Consumption in Relation to Quality of Life among Finnish Female Municipal Employees: A Cross-Sectional Study - Bergman Elina; Vepsäläinen Henna; Erkkola Maijaliisa; Laaksonen Marika; Kautiainen Hannu; Penttinen Markus A; Rautava Päivi; Korhonen Päivi E (MDPI, 2022)
Aspects of good quality of life (QoL) have been found to motivate people to make lifestyle changes. There is also evidence that certain dietary patterns are associated with QoL. The aim of this work was to examine whether consumption frequencies of healthy and unhealthy food items are associated with QoL in female employees. A cross-sectional study was conducted among 631 Finnish female employees (mean age 49 years, SD = 10) from 10 municipal work units in 2015. Information about the participants was collected by physical examination, laboratory tests, self-administered questionnaires, including the Food Frequency Questionnaire (FFQ), and from medical history. QoL was assessed with the EUROHIS-Quality of Life 8-item index. A significant positive association was seen between consumption frequency of healthy foods and the EUROHIS-QOL mean score (p = 0.002). The association was small but comprehensive, also involving most dimensions of QoL. The consumption frequency of unhealthy foods was not associated with QoL. These findings are relevant when designing diet counselling, since QoL is an outcome that has been found to motivate people to change their health habits. Recommending abundant use of healthy foods could be a simple and convenient way of diet counselling at many health care appointments, where time consuming approaches are difficult to conduct.